Normative data and comprehensive psychometric evaluation of the Hogg Eco-Anxiety Scale in a large Italian sample - Giuseppina Spano; Elisabetta Ricciardi; Luigi Tinella; Alessandro O. Caffò; Giovanni Sanesi; Andrea Bosco (Heliyon)
As the climate crisis intensifies, its impact on mental health becomes more apparent, leading to psychological distress such as eco-anxiety. Driven by growing scientific interest, standardized assessment tools for evaluating eco-anxiety are gaining traction. This study comprehensively validates the Hogg Eco-Anxiety Scale (HEAS) on a large sample of nearly 1300 participants across Italy and four generations. The scores obtained using the Italian HEAS demonstrate excellent reliability and support valid inferences regarding eco-anxiety levels. The original four-factor structure of the scale was upheld. Nonetheless, the scale proved to be reliable also in terms of a unique factor. Internal consistency was satisfactory, but stability over three months was not confirmed. The overall HEAS score was linked to pro-environmental behavior and reduced meat consumption. Additionally, the scale effectively identifies individuals engaged in public pro-environmental actions. Normative data were provided for age, gender, and education levels. These findings confirmed and extended the HEAS's validity and reliability, highlighting the importance of standardized assessment tools in this burgeoning research field and in clinical practice. Further exploration of its diagnostic efficacy in clinical settings for eco-anxiety detection is suggested.